An Ecological Study of Free-living Marine Nematodes in Teluk Awar, Sarawak, Malaysia - Chen, Cheng-Ann; Shabdin, Mohd Long; Norliana, Mohd Rosli (Universiti Malaysia Sarawak (UNIMAS), 2012)
The community structure of marine nematode assemblages in the southern-west of Borneo was investigated with special focus on the horizontal distribution from high tide to subtidal area. A transect study had been conducted in Teluk Awar. Nine stations were chosen from the Mean High Water Neap to Mean Low Water Neap level. The physico-chemical characteristic of water and sediments were determined both ex situ. One-way ANOVA showed that the environmental variables among stations were significantly different (except chlorophyll a and total organic matter). Multi-dimensional scaling demonstrated three distinct patterns among the stations while dendrogram showed high dissimilarity percentage in the species distribution among stations. In conclusion, the results showed that environmental variables such as clay, total organic matter and temperature were affecting the nematode distribution pattern in Teluk Awar.